Implementation of PPPK Policy for Elementary School Teachers in Civil Service Management Reform - Lutfia Syafrudin; Mohammad Sofwan Effendi; Muh. Takdir; Syafa’at Ariful Huda (Journal of Educational Sciences, 2026)
This study examines the implementation of the Government Employees with Work Agreements (PPPK) policy for elementary school teachers within the context of civil service management reform, with a focus on teacher professionalism and educational governance. A systematic literature review was conducted using the PRISMA framework, supported by bibliometric analysis through VOSviewer to identify research trends, keyword networks, and gaps in the literature. The findings indicate that the PPPK policy has contributed to strengthening teacher professionalism through improved employment security, reinforcement of the merit system, and expanded access to competency development. Bibliometric results show a significant increase in related publications following the enactment of Government Regulation Number 49 of 2018, particularly on issues of teacher assignment, performance, and ASN governance. Nevertheless, policy implementation faces persistent challenges, including regional disparities, unequal teacher distribution, and the absence of standardized performance evaluation mechanisms for PPPK teachers at the elementary level. This study highlights the need for comprehensive empirical evaluation, stronger central–local policy alignment, and an integrated career management and performance monitoring framework to enhance the effectiveness of ASN reform in the education sector.